PERSEPSI MASYARAKAT BIDAR ALAM TENTANG PENERAPAN PERDA KABUPATEN SOLOK SELATAN NO. 1 TAHUN 2020 DALAM MENGATASI KONFLIK ANTARA PEMILIK HEWAN TERNAK DENGAN PEMILIK LAHAN - ROMI MESRA; Rus Yandi; Rifka Zuwanda; Basrial Zuhri; Afriendi Sikumbang (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Before proceeding to the process of overcoming conflict, basically a conflict can be prevented, it can be detected by the community and the local government, which are called symptoms of conflict. In general, this conflict occurs because of livestock entering the community's productive lands, such as rice fields planted with rice, gardens planted with rubber seeds, gardens planted with oil palm, and community productive lands planted with various other crops. People certainly don't want their crops to be damaged and even potentially crop failure, while those who own livestock are usually difficult to compromise. The research approach used in this study is a qualitative research approach. Data collection techniques in this study were conducted by interview and observation. Data analysis techniques in this study use data analysis techniques Miles and Hubermen, including data reduction (data reduction), data presentation (data display) and drawing conclusions and verification (conclusion drawing / verification). The results of this study are: not many people know about the regional regulation, the regional regulation has not been implemented in conflict resolution, and the community still applies the "law of the jungle".